1975
DOI: 10.1007/bf01868565
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-potassium-stimulated net potassium efflux from human erythrocyte ghosts

Abstract: In the presence of 8 mM external Ca++, the K+ permeability of human red cell ghosts increases provided K+ is also present in the medium. This increase does not represent K+/K+ exchange but a stimulation of net K+ efflux. The stimulation is half-maximal at 0.7 +/- 0.15 mM (n=5). At concentrations above 4.0 mM, external K+ inhibits net K+ efflux. Similar stimulatory and inhibitory effects of external K were also observed in intact cells after exposure to Pb++ or to Ca++ in the presence of fluoride, iodoacetate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
1

Year Published

1978
1978
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 24 publications
6
18
1
Order By: Relevance
“…8 are consistent with previous descriptions of Na activation of K efflux (Knauf et al 1975;Hoffman & Blum, 1977), and activation of Ca-dependent K efflux by Ko has been studied in ATP-depleted cells (Kregenow & Hoffman, 1972;Hoffman & Blum, 1977) and in red cell ghosts (Knauf et al, 1975;Simons, 1979;Heinz & Passow, 1980). The dependence on Ko illustrated by the results in Fig.…”
Section: K Efflux Has Previously Been Briefly Described -4 (Hoffmansupporting
confidence: 89%
See 2 more Smart Citations
“…8 are consistent with previous descriptions of Na activation of K efflux (Knauf et al 1975;Hoffman & Blum, 1977), and activation of Ca-dependent K efflux by Ko has been studied in ATP-depleted cells (Kregenow & Hoffman, 1972;Hoffman & Blum, 1977) and in red cell ghosts (Knauf et al, 1975;Simons, 1979;Heinz & Passow, 1980). The dependence on Ko illustrated by the results in Fig.…”
Section: K Efflux Has Previously Been Briefly Described -4 (Hoffmansupporting
confidence: 89%
“…This stimulation of efflux by WW 781 is problematical for a quantitative analysis correlating fluxes and voltages. The inhibitory effect of K o on ~ contrasts with the stimulatory effect of K o on valinomycin-mediated K effiux (Hunter, 1977;Wieth & Tosteson, 1979), and agrees with previous studies of the Gardos effect in ATP-depleted cells (Blum & Hoffman, 1971;Kregenow & Hoffman, 1972;Hoffman & Blum, 1977) as well as in ghosts (Knauf et al, 1975;Heinz & Passow, 1980).…”
Section: Effect Of Ww 781 On Ca-induced Rb Effluxsupporting
confidence: 87%
See 1 more Smart Citation
“…In these experiments we manipulated the Na + and K + chemical potential gradients by varying the extracellular Na + and K + concentrations. However, it has been shown for erythrocytes that the CaZ+-activated K + permeability is sensitive to the concentration of extracellular K + (Knauf et al, 1975). Recent studies have shown also that in other cell types, CaZ+-activated K + channels are voltage sensitive (Gorman & Thomas, 1980;Hermann & Hartung, 1982b;Barrett, Magleby & Pallotta, 1982).…”
Section: Evidence For the Existencementioning
confidence: 98%
“…Another possible consequence of Em effects on Gardos channel activity concerns the relationship between K+ effiux and K+. It has been reported (12, [36][37][38][39]) that activation of Ca2+-dependent K+ transport is biphasic, reaching peak activity at 2-3 mM K+ and then falling off as K+ is increased further. This is the situation in the absence of DIDS whether the principal anion is Cl-or SOt-.…”
Section: Discussionmentioning
confidence: 99%